Pseudohypoparathyroidism type I‐b with neurological involvement is associated with a homozygous PTH1R mutation. (24th August 2016) - Guerreiro, R.; Brás, J.; Batista, S.; Pires, P.; Ribeiro, M. H.; Almeida, M. R.; Oliveira, C.; Hardy, J.; Santana, I.
Abstract : Pseudohypoparathyroidism type 1b (PHP1b) is characterized by hypocalcemia, hyperphosphatemia, increased levels of circulating parathyroid hormone (PTH), and no skeletal or developmental abnormalities. The goal of this study was to perform a full characterization of a familial case of PHP1b with neurological involvement and to identify the genetic cause of disease. The initial laboratory profile of the proband showed severe hypocalcemia, hyperphosphatemia and normal levels of PTH, which was considered to be compatible with primary hypoparathyroidism. With disease progression the patient developed cognitive disturbance, PTH levels were found to be slightly elevated and a picture of PTH resistance syndrome seemed more probable. The diagnosis of PHP1b was established after the study of family members and blunted urinary cAMP results were obtained in a PTH stimulation test. Integration of whole genome genotyping and exome sequencing data supported this diagnosis by revealing a novel homozygous missense mutation in PTH1R (p.Arg186His) completely segregating with the disease. Here, we demonstrate segregation of a novel mutation in PTH1R with a phenotype of PHP1b presenting with neurological symptoms, but no bone defects. This case represents the extreme end of the spectrum of cognitive impairment in PTH dysfunction and defines a possible novel form of PHP1b resulting from the impaired interaction between PTH and PTH1R. Abstract : Identification of the homozygous p.Arg186His mutation in PTH1R as associated with Pseudohypoparathyroidism Type I‐b with neurological involvement in a Portuguese family.